COMPORTEMENT SEXUEL A RISQUE DES JEUNES SCOLARISÉS: UNE ANALYSE DES DETERMINANTS SOCIAUX DU NON-USAGE DU PRÉSERVATIF27 CHEZ LES ÉLÈVES DU LYCÉE MODERNE II DE BOUAKÉ - Hilaire, Mazou Gnazegbo (European Scientific Journal, ESJ, 2014)
This paper means to help understand and analyse the paradox about the use of condom for the lowering of sexually transmitted infections, unwilling pregnancies, and the young’s reluctance to use condom, especially those attending the secondary school called Lycée Moderne II de Bouakéalthough these young students are extremely exposed to the risks of careless sex. Although the pupils of Lycée Moderne II in Bouaké, Côte d’Ivoire, develop awareness of the important role of condom in terms of risk prevention linked with sex, they do not systematically resort to it during sex intercourses. It therefore appears that the use of condom as a common practice is not well adopted by these students of the lycée Moderne II in Bouaké, as they do not necessarily establish the link between the use of condom and the prevention of sexually transmitted infections.